lslam and modernity: a brief elucidation of Nasr's position on lslamic and modern science and philosophy - Owoyemi, Musa Yusuf (International Research Journal, 2012)
The debate on lslam and Modernity continues to be an interesting one especially as it concerns the area of science and philosophy which are the two most important shapers of the contemporary modern world-view. Likewise, the debate on whether there is lslamic science and philosophy or not is an on going one in the Muslim world as some Muslim modernists, like Pervez Hoodbhoy, have taken the position that there is nothing like lslamic science and philosophy.It is therefore pertinent at this time of confusion and miscommunication to highlight, especially to the Muslim Youths and intellectuals who are interested in the study of Islam, what constitute lslamic science and philosophy and why it is different from what is known today as modern science and philosophy.It is in the light of the above that this paper intends to bring to fore the meaning of lslamic science and philosophy and how it is different from modern science and philosophy by looking at the work of one of the contemporary Muslim philosopher, Seyyed Hossein Nasr, and how, in his view, lslamic science and philosophy are different from modern science and philosophy.